2023
DOI: 10.1101/2023.01.16.523975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A dual MTOR/NAD+ acting gerotherapy

Abstract: The geroscience hypothesis states that a therapy that prevents the underlying aging process should prevent multiple aging related diseases. The mTOR (mechanistic target of rapamycin)/insulin and NAD+ (nicotinamide adenine dinucleotide) pathways are two of the most validated aging pathways. Yet, it's largely unclear how they might talk to each other in aging. In genome-wide CRISPRa screening with a novel class of N-O-Methyl-propanamide-containing compounds we named BIOIO-1001, we identified lipid metabolism cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It has been recently reported that natural products, including phenols, flavonoids, glycosides, quinones, terpenoids, pyrazines, alkaloids, and phenylpropanoids, have antioxidant, energy-producing, anti-inflammatory, anti-apoptotic, and anti-aging effects, which mainly influence the AMPK/Nrf2/mTOR, Nrf2/HO-1, NAMPT/NAD(+)/SIRT, AMPK/SIRT1/PGC-1alpha and PKCs/PARPs/NF-kB signaling pathways, thereby regulating NAD(+) metabolism to prevent and treat NAFLD [ 117 ]. Hepatoprotective effects, caused by the inhibition of PI3K/Akt/mTOR signaling and effective alleviation of oxidative stress damage and ER stress induced by excessive lipid accumulation in hepatocytes, and activation of autophagy were observed for agonists of AMPK thymoquinone [ 118 ] and 5-aminoimidazole-4-carboxamide-1-beta-D-ribofuranoside (AICAR) [ 119 ], agonist of GLP-1/glucagon cotadutide [ 120 ], an antagonist of sphingosine 1-phosphate receptor 2 (S1PR2) JTE-013 [ 26 ], activator of PI3K, autophagy-related genes (ATG) and agonist of Nrf2, PPARα and hemeoxygenase-1 (HO-1) pterostilbene [ 121 ], flavonoid with antioxidant properties involving CYP7A1, quercetin [ 122 ], Pueraria flavonoids [ 92 ], a novel gerotherapy compound, BIOIO-1001 [ 123 ], a natural nonenzymatic antioxidant with low toxicity schisandrin B (Sch B) [ 124 ], H1-antihistamines (AHs) [ 125 ], fat soluble polyphenol Tanshinone IIA (TsIIA) [ 126 ], purendan (PRD) [ 127 ], down-regulating the expression of p-mTOR, p-S6K1 and SREBP-1c, chrysin [ 128 ], red pepper seed extract (RPS) [ 129 ], Gardenia Fructus (GF) extracts [ 130 ], curcumin [ 131 ], and magnesium [ 132 ].…”
Section: New Therapeutic Approaches and Molecular Targets In Nafld/na...mentioning
confidence: 99%
“…It has been recently reported that natural products, including phenols, flavonoids, glycosides, quinones, terpenoids, pyrazines, alkaloids, and phenylpropanoids, have antioxidant, energy-producing, anti-inflammatory, anti-apoptotic, and anti-aging effects, which mainly influence the AMPK/Nrf2/mTOR, Nrf2/HO-1, NAMPT/NAD(+)/SIRT, AMPK/SIRT1/PGC-1alpha and PKCs/PARPs/NF-kB signaling pathways, thereby regulating NAD(+) metabolism to prevent and treat NAFLD [ 117 ]. Hepatoprotective effects, caused by the inhibition of PI3K/Akt/mTOR signaling and effective alleviation of oxidative stress damage and ER stress induced by excessive lipid accumulation in hepatocytes, and activation of autophagy were observed for agonists of AMPK thymoquinone [ 118 ] and 5-aminoimidazole-4-carboxamide-1-beta-D-ribofuranoside (AICAR) [ 119 ], agonist of GLP-1/glucagon cotadutide [ 120 ], an antagonist of sphingosine 1-phosphate receptor 2 (S1PR2) JTE-013 [ 26 ], activator of PI3K, autophagy-related genes (ATG) and agonist of Nrf2, PPARα and hemeoxygenase-1 (HO-1) pterostilbene [ 121 ], flavonoid with antioxidant properties involving CYP7A1, quercetin [ 122 ], Pueraria flavonoids [ 92 ], a novel gerotherapy compound, BIOIO-1001 [ 123 ], a natural nonenzymatic antioxidant with low toxicity schisandrin B (Sch B) [ 124 ], H1-antihistamines (AHs) [ 125 ], fat soluble polyphenol Tanshinone IIA (TsIIA) [ 126 ], purendan (PRD) [ 127 ], down-regulating the expression of p-mTOR, p-S6K1 and SREBP-1c, chrysin [ 128 ], red pepper seed extract (RPS) [ 129 ], Gardenia Fructus (GF) extracts [ 130 ], curcumin [ 131 ], and magnesium [ 132 ].…”
Section: New Therapeutic Approaches and Molecular Targets In Nafld/na...mentioning
confidence: 99%